Evaluation of Handwritings of Identical Twins by Forensic Handwriting Principles - Türedi, Behice Şeyda (The Bulletin of Legal Medicine, 2017)
Objective: In the field of forensic science, one of the most noteworthy topics about identical twins is hand writing. In this study; It is aimed to determine the degree of similarity of the handwritings of the identical twins and to evaluate the effect of the genetic similarities in terms of examination of the judicial documents. Materials and Methods: In our study; “Atatürk’ün Gençliğe Hitabesi”- “Atatürk’s Speech to Youth” is printed on 100 voluntary adults. Letters “a, b, d, g, m, r, ş, u, v, y, z” were examined with the aid of a magnifying glass and ruler. Results: There were no statistically significant differences in the similarity rates of the handwritten characters with the variables analyzed (gender of twins, age, occupation of the same profession, same level of education, residence time in the same household, frequency of use of writing, (p>0.05). The letter “d” (56%) used by 50 twin pairs was used as the most similar letter, and the letter “m” (14%) was used as the least similar letter. It has been found that the handwritings of female couples show more similarity than male couples. The similarity rates of female twins in their handwriting were 90.9% maximum, minimum 0%; The similarity ratios of the male twins to the handwriting maximum: 54.54%, minimum 0%. Conclusion: Even though the handwriting is highly similar in our work, we have achieved results that support the scientific truth that the two handwriting cannot be quite similar. The results are important in terms of diagnostic features in the identification of handwritings.